Estudio de factibilidad para la creación de una comercializadora en línea maquillaje y servicio de peinados para mujeres afro-descendientes, en la ciudad de Cali, Valle del Cauca (2013)
This work intends to market cosmetics line for women of African descent and the provision of hairstyles (braids and extension), because women in the world today are seeking effective and quickest ways to improve your quality of life and personal presentation with products in addition to providing a solution to a particular situation, provide safety and comfort you need to live everyday to the fullest. With the creation of the Global CENTER FOR COSMETIC AFROLATINO SAS seeks to achieve the Afro- descendant women to find the right way to enhance their beauty offering specialized for different skin tones of this population, consistent with the trends and add up their individual characteristics enabling it to project a better image to others and to themselves. This cosmetic and personal care sector has been characterized by a compound annual growth of 8.7 % between 2006-2014 , according Proexport Colombia will remain as one of the growth engines of the Latin American market , as it has for female labor participation Positions highest management of Colombia is an attractive country to cover this niche , growth in this sector which is seen as one of the world class sectors of the economy of the country is contrasted with the need to fragment the market based exclusively on the Afro- descendant population of the city of Santiago de Cali. The African populations in Colombia represent 10.6%, the 4,316,592 people. Cali, with 26.2 percent of afros, is the city where this breed is more concentrate, that’s why the marketing is an alternative to promote products because ethnicity is a little explored by manufacturing, trade and services due to lack of studies and investments is this population.